Short Chain Fatty Acids Prevent Glyoxylate-Induced Calcium Oxalate Stones by GPR43-Dependent Immunomodulatory Mechanism - Jin, Xi; Jian, Zhongyu; Chen, Xiaoting; Ma, Yucheng; Ma, Hongwen; Liu, Yu; Gong, Lina; Xiang, Liyuan; Zhu, Shiyu; Shu, Xiaoling; Qi, Shiqian; Li, Hong; et al. (Frontiers in Immunology, 2021)
Calcium oxalate (CaOx) stones are the most common type of kidney stones and are associated with high recurrence, short chain fatty acids (SCFAs), and inflammation. However, it remains uncertain whether SCFAs affect the formation of CaOx stones through immunomodulation. We first performed mass cytometry (CyTOF) and RNA sequencing on kidney immune cells with glyoxylate-induced CaOx crystals (to elucidate the landscape of the associated immune cell population) and explored the role of SCFAs in renal CaOx stone formation through immunomodulation. We identified 29 distinct immune cell subtypes in kidneys with CaOx crystals, where CX3CR1+CD24- macrophages significantly decreased and GR1+ neutrophils significantly increased. In accordance with the CyTOF data, RNA sequencing showed that most genes involved were related to monocytes and neutrophils. SCFAs reduced kidney CaOx crystals by increasing the frequency of CX3CR1+CD24- macrophages and decreasing GR1+ neutrophil infiltration in kidneys with CaOx crystals, which was dependent on the gut microbiota. GPR43 knockdown by transduction with adeno-associated virus inhibited the alleviation of crystal formation and immunomodulatory effects in the kidney, due to SCFAs. Moreover, CX3CR1+CD24- macrophages regulated GR1+ neutrophils via GPR43. Our results demonstrated a unique trilateral relationship among SCFAs, immune cells, and the kidneys during CaOx formation. These findings suggest that future immunotherapies may be used to prevent kidney stones using SCFAs.